Determination some thermo-physical and metallurgical properties of aluminum alloys using their known chemical composition. (August 2019) - Huber, Gerhard; Djurdjevic, Mile B.; Manasijevic, Srecko
Highlights: Simulation is presently routinely applied in many aluminium foundries as a standard tool. Available databases currently used only a few selected standard alloys. The accuracy of casting simulation depends on the quality of available software's database. The approach in this paper is based on the silicon equivalency procedure. Abstract: Simulation is currently routinely applied in many aluminum foundries as a standard tool. The accuracy of casting simulation depends to a large extent on the quality of the available physical and thermo-physical properties of the material provided by the software's database. The available databases presently used in commercial simulation software packages for the casting industry are usually equipped with material properties only for a few selected standard alloys. This paper offers an alternative approach that could be used to determine some required thermo-physical and structural properties for the simulation of cast aluminum alloys. The approach is based on the silicon equivalency procedure which numerically expresses the impact of all alloying elements through the equivalent content of silicon. This paper illustrates the applicability of this approach for cast Al–Si series of alloys.